Real-time Monitoring of Internal Temperature and Voltage of High-temperature Fuel Cell Stack. (10th April 2015) - Lee, Chi-Yuan; Weng, Fang-Bor; Huang, Yen-Pu; Chang, Chih-Ping; Cheng, Chih-Kai
Abstract: The nonuniform local temperature and voltage in the chemical reaction process of high-temperature proton exchange membrane fuel cell (HT-PEMFC) stack can affect the reaction of membrane electrode assembly (MEA) and the performance and life of fuel cell stack. The effectiveness and internal information of fuel cell stack can be discussed by using external measurement, invasive, theoretical modeling, and single temperature, or voltage measurement. But there are some problems, such as mm scale sensor, inaccurate measurement, influencing the fuel cell stack performance, and failing to know internal actual reactive state instantly. This study uses micro-electro-mechanical systems (MEMS) technology to develop a new generation flexible micro temperature and voltage sensors applicable to high-temperature electrochemical environment. Micro sensors have embedded in the cathode channel plate of HT-PEMFC stack. At the operating temperature of 170 °C and constant current (2, 10, 20 A), the curvilinear trends of local temperature and voltage inside the fuel cell stack measured by flexible micro sensors are consistent, proving the reliability of micro sensors. The test result also shows that the heat distribution in the fuel cell stack is nonuniform.